Anti-cutting glove and preparation method thereof

The impregnant materials prepared by mixing polyurethane emulsions and other materials, bonding the skin comfort layer and the cutting-resistant layer, and drying and curing in a vacuum drying box to form an wear-resistant glue layer, solving the insufficient protective performance of traditional anti-cut gloves. and the problem of poor comfort achieves efficient anti-cutting and wear resistance.

CN119453602AActive Publication Date: 2025-02-18WUXI GUANGDALONG TEXTILE CO LTD

Patent Information

Application Number
CN202411589107.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Traditional anti-cut gloves lack protection when cutting sharp objects, especially weak protection for fingers and palms, and are rigid in design, and have poor wearing comfort.

Method used

Using polyurethane emulsion, nitrile latex, modified nanozirconia, crosslinking agent, surfactant and thickener, etc., the impregnated gel is obtained by mixing and mixing, and the skin comfort layer and the cutting-resistant layer are bonded to form gloves. The embryo is fenced and dried and solidified in a vacuum drying box to form an wear-resistant glue-impregnation layer.

Benefits of technology

It significantly improves the anti-cutting performance and wear resistance of the gloves, while improving the comfort and flexibility of the gloves, ensuring excellent fit and safety during high-strength operations.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of anti-cutting gloves, in particular to an anti-cutting glove and a preparation method thereof, which are used for solving the problems of insufficient protection performance and poor comfort of the existing anti-cutting glove. The anti-cutting glove comprises a skin-attaching comfortable layer, a cutting-resistant layer and a wear-resistant gum dipping layer, the skin-attaching comfortable layer enables the glove to have excellent comfort and not prone to causing hand pressure, the cutting-resistant layer can effectively improve the cutting-resistant performance of the glove, the cutting-resistant capability of the glove is greatly enhanced, sharp instruments are prevented from easily penetrating through the glove, the hand safety is effectively protected, the wear-resistant gum dipping layer can effectively improve the sealing performance and wear resistance of the glove, and the service life of the glove is prolonged. The durability and the stability of the glove are improved; the anti-cutting gloves prepared by the preparation method not only can effectively protect the safety of hands, but also can keep excellent fitting degree and flexibility even when high-strength operation is carried out, so that an operator can smoothly complete tasks in a complex environment, and the working efficiency and the safety are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of cut-resistant gloves, and in particular to a cut-resistant glove and a preparation method thereof. Background Art

[0002] In many fields such as industrial production, construction, and mechanical operation, workers' hand safety faces various potential dangers. With the increasing requirements for personal protection in industrial production and daily life, cut-resistant gloves have become an important equipment to reduce physical injuries in the working environment. However, traditional gloves usually have insufficient protection when facing the cutting of sharp objects, especially the protection of fingers and palms is relatively weak, which can easily lead to accidental cuts and injuries. In addition, most of the cut-resistant gloves on the market are relatively rigid in design and not comfortable to wear, which can easily affect users when performing delicate operations. Therefore, it is of great significance to develop a cut-resistant glove and a preparation method thereof that has excellent cut-resistant performance and can maintain high flexibility and comfort. Summary of the invention

[0003] In order to overcome the above technical problems, the object of the present invention is to provide a cut-resistant glove and a preparation method thereof, wherein polyurethane emulsion, nitrile latex, modified nano zirconium oxide, a cross-linking agent, a surfactant and a thickener are added to a mixer and stirred to obtain a dipping material, a skin-contacting comfort layer and a cut-resistant layer are bonded to form a glove blank, and the glove blank is immersed in a coagulant, taken out and immersed in the dipping material, and then dried and cured to form a wear-resistant dipping layer to obtain a cut-resistant glove, thereby solving the problem that the existing cut-resistant gloves have insufficient protective performance and poor comfort.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A cut-resistant glove, comprising, from inside to outside, a skin-contacting comfort layer, a cut-resistant layer, and a wear-resistant dipped rubber layer;

[0006] Wherein, the cut-resistant layer is prepared by the following steps:

[0007] Step s1: add p-methoxybromobenzene, p-methoxyaniline, bis(triphenylphosphino)acetate palladium(II), 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, tert-butyl potassium and N,N'-dimethylacetamide to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 100-110°C and continue to stir and react for 3-4 hours, then heat to 160-170°C and continue to stir and react for 4-5 hours, after the reaction is completed, cool the reaction product to room temperature, then add it to ice water, then let it stand to precipitate, then centrifuge, and recrystallize the precipitate from anhydrous methanol to obtain an intermediate;

[0008] Step s2: adding the intermediate and chloroform to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stirring the reaction for 40-50 minutes at a temperature of -5-0°C and a stirring rate of 300-400 r / min, then adding boron tribromide dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir the reaction for 8-10 hours after the dropwise addition is completed. After the reaction is completed, adding the reaction product to ice water, then vacuum filtering, washing the filter cake with distilled water for 2-3 times, then placing it in a vacuum drying oven, and drying it at a temperature of 70-75°C for 2-3 hours to obtain a hyperbranched monomer;

[0009] Step s3: add a hyperbranched monomer, bisphenol AF, 2,6-dichlorobenzonitrile, anhydrous potassium carbonate, N-methylpyrrolidone and toluene into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 1-2 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heat to 140-150° C. and continue to stir and react for 3-4 hours, then heat to 190-200° C. and continue to stir and react for 3-4 hours, after the reaction is completed, cool the reaction product to room temperature, then add it to a hydrochloric acid solution, then stand it to precipitate, then centrifuge it, wash the precipitate with distilled water 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 90-100° C. for 2-3 hours to obtain a performance coating resin;

[0010] Step s4: Add the performance coating resin, propylene glycol and N, N'-dimethylacetamide into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 3-4 hours at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add the carbon fiber cloth and ultrasonically treat it for 2-3 hours at an ultrasonic power of 100-150W, then let it stand for 3-5 hours, then place it in a vacuum drying oven, and dry it at a temperature of 80-85°C for 8-10 hours to obtain a cut-resistant layer.

[0011] As a further scheme of the present invention: the dosage ratio of the p-methoxybromobenzene, p-methoxyaniline, bis(triphenylphosphino)acetate palladium(II), 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, tert-butyl potassium and N,N'-dimethylacetamide in step s1 is 20mmol:10mmol:0.1-0.12g:0.18-0.22g:2.8-3.6g:50-55mL.

[0012] As a further solution of the present invention: the usage ratio of the intermediate, chloroform and boron tribromide in step s2 is 10 mmol:40-50 mL:4.8-6.6 mL.

[0013] As a further scheme of the present invention: the usage ratio of the hyperbranched monomer, bisphenol AF, 2,6-dichlorobenzonitrile, anhydrous potassium carbonate, N-methylpyrrolidone and toluene in step s3 is 0.1-0.3 mol: 0.04-0.06 mol: 0.5 mol: 0.2-0.5 mol: 180-200 mL: 100-120 mL.

[0014] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step s3 is 5-7%.

[0015] As a further solution of the present invention: the usage ratio of the performance coating resin, glycerol, N,N'-dimethylacetamide and carbon fiber cloth in step s4 is 2g:0.05-0.1g:80-90mL:5g.

[0016] As a further solution of the present invention: the carbon fiber cloth in step s4 is Toray PAN-P-1.5K plain weave carbon fiber woven cloth with a thickness of 0.18 mm.

[0017] As a further solution of the present invention: a method for preparing cut-resistant gloves comprises the following steps:

[0018] Step 1: Weigh 40-50 parts of polyurethane emulsion, 26-42 parts of nitrile latex, 1.8-10.2 parts of modified nano zirconium oxide, 0.2-0.6 parts of cross-linking agent, 1-3 parts of surfactant and 1-5 parts of thickener according to weight parts, and set aside;

[0019] Step 2: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing for 1-2 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min to obtain a dipping material;

[0020] Step 3: Bond the skin-friendly comfort layer and the cut-resistant layer to form a glove blank, and immerse the glove blank in a coagulant, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at a temperature of 60-65°C for 35-40 minutes, then heat it to 125-130°C and dry it for 1-1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

[0021] As a further solution of the present invention: the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; and the thickener is sodium carboxymethyl cellulose.

[0022] As a further solution of the present invention: the skin-contacting comfort layer is one of polyester fabric, cotton fabric, linen fabric, acrylic fabric and nylon fabric.

[0023] As a further solution of the present invention: the coagulant is a mixed solution of calcium nitrate and methanol in a mass ratio of 1-10g:95g.

[0024] As a further solution of the present invention: the modified nano zirconium oxide is prepared by the following steps:

[0025] Step a1: Add hydroquinone, triethylamine and anhydrous tetrahydrofuran into a four-necked flask equipped with a stirrer, a thermometer, an air guide tube, a reflux condenser and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add isocyanatepropyltriethoxysilane solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 10-15 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then eluted with a mixed solvent to obtain a strong modifier;

[0026] Step a2: Add nano zirconium oxide powder and toluene to a three-necked flask equipped with a stirrer and a thermometer, perform ultrasonic treatment for 20-30 minutes at an ultrasonic power of 300-350W, then add a strong modifier solution and continue ultrasonic treatment for 5-10 minutes, then stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30 minutes, then heat the temperature to 80-85°C and continue stirring the reaction for 1-2 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with methanol 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 1-1.5 hours to obtain modified nano zirconium oxide.

[0027] As a further solution of the present invention: the usage ratio of the hydroquinone, triethylamine, anhydrous tetrahydrofuran and isocyanatepropyltriethoxysilane solution in step a1 is 10 mmol: 0.01-0.02 g: 50-55 mL: 20-25 mL.

[0028] As a further solution of the present invention: the isocyanate triethoxysilane solution in step a1 is a solution formed by dissolving isocyanate triethoxysilane in anhydrous tetrahydrofuran at a ratio of 10 mmol:10 mL; the mixed solvent is a mixture of petroleum ether and ethyl acetate at a volume ratio of 25-30:1.

[0029] As a further solution of the present invention: the dosage ratio of the nano zirconium oxide powder, toluene and strong modifier solution in step a2 is 2g:15-20mL:10-15mL.

[0030] As a further solution of the present invention: the average particle size of the nano zirconium oxide powder in step a2 is 50nm; the strong modifier solution is a mixture formed by dissolving the strong modifier in ethanol solution at a ratio of 1g:8-10g, and the volume fraction of the ethanol solution is 85-90%.

[0031] Beneficial effects of the present invention:

[0032] The invention discloses a cut-resistant glove and a preparation method thereof. The invention comprises the following steps: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, a cross-linking agent, a surfactant and a thickener into a mixer and stirring and mixing the mixture to obtain a dipping material; bonding a skin-contacting comfort layer and a cut-resistant layer to form a glove blank; and dipping the glove blank into a coagulant, taking the glove blank out and dipping the dipping material, drying the glove blank, and curing the glove blank to form a wear-resistant dipping layer to obtain the cut-resistant glove. The cut-resistant glove comprises a skin-contacting comfort layer, a cut-resistant layer and a wear-resistant dipping layer from the inside to the outside, wherein the skin-contacting comfort layer can make the glove have excellent The cut-resistant layer can effectively improve the anti-cutting performance of the gloves, greatly enhance the anti-cutting ability of the gloves, prevent sharp objects from easily penetrating, and effectively protect the safety of the hands. The wear-resistant impregnated layer can effectively improve the sealing and wear resistance of the gloves, and improve the durability and stability of the gloves. The cut-resistant gloves prepared by this preparation method can not only effectively protect the safety of the hands, but also enable the gloves to maintain excellent fit and flexibility even during high-intensity operations, ensuring that the operator can successfully complete the task in a complex environment, and significantly improving work efficiency and safety.

[0033] In the process of preparing the cut-resistant gloves, a cut-resistant layer is first prepared. First, p-methoxybromobenzene and p-methoxyaniline are reacted, and the bromine atom on the p-methoxybromobenzene reacts with -NH2 and -NH- in sequence to form an intermediate containing three benzene rings and a methoxy group. Then, the methoxy group on the intermediate forms a hydroxyl group under the action of boron tribromide to obtain a hyperbranched monomer. Then, the hyperbranched monomer, bisphenol AF, and 2,6-dichlorobenzonitrile are used as polymerization monomers to form a polyarylethernitrile containing a large number of CF bonds and hyperbranching to obtain a performance coating resin. Then, the performance coating resin is dissolved and coated on a carbon fiber cloth to obtain a cut-resistant layer. The carbon fiber cloth is a high-strength, high-modulus fiber material that can greatly improve the cut and puncture resistance of the gloves. The performance coating resin is used to After coating, the cyano group on it has strong polarity, which makes the carbon fiber cloth and the performance coating resin have excellent bonding effect. The molecular structure of the performance coating resin contains a large number of benzene rings, which can give it excellent mechanical strength, and can further improve the anti-cutting and puncture performance of the carbon fiber cloth. The introduction of a large number of CF bonds can make the carbon fiber cloth resist the erosion of various corrosive substances, improve its chemical resistance, enable it to maintain high performance in harsh environments, improve the safety of the anti-cut gloves, and increase the bonding strength of the cut-resistant layer with the skin-friendly comfort layer and the wear-resistant impregnated layer, improve the integrity and stability of the cut-resistant layer, so that the carbon fiber cloth can more effectively disperse and transfer stress when subjected to external force, thereby significantly improving the anti-cutting performance of the anti-cut gloves.

[0034] In the process of preparing the anti-cutting gloves, a modified nano-zirconia is also prepared. First, hydroquinone and isocyanatepropyltriethoxysilane are reacted, and the hydroxyl group on the hydroquinone reacts with the isocyanate group on the isocyanatepropyltriethoxysilane to form a strong modifier containing a large number of siloxane groups. Then, the nano-zirconia powder is treated with the strong modifier. After the strong modifier is hydrolyzed, the siloxane on it is converted into silanol and grafted onto the particle surface of the nano-zirconia powder to obtain modified nano-zirconia. Zirconia is an inorganic material with high hardness, high wear resistance and high chemical stability. After being added to the wear-resistant dipping layer, it gives it an excellent wear-resistant enhancement effect. After the nano-zirconia powder is modified, the dispersibility of the nano-zirconia powder can be improved, and a large number of silanol groups are introduced so that it can be connected to other components of the dipping material in the form of chemical bonds, thereby improving the overall uniformity and wear resistance of the wear-resistant dipping layer, making the wear-resistant dipping layer not easily worn and damaged, protecting the integrity of the internal structure of the gloves, and further improving the safety and durability of the anti-cutting gloves. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Embodiment 1:

[0037] This embodiment is a method for preparing cut-resistant gloves, comprising the following steps:

[0038] Step S1: 10mmol hydroquinone, 0.01g triethylamine and 50mL anhydrous tetrahydrofuran are added to a four-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred and reacted for 20min at a temperature of 25°C and a stirring rate of 300r / min. Then, 20mL of an isocyanatepropyltriethoxysilane solution formed by dissolving isocyanatepropyltriethoxysilane in anhydrous tetrahydrofuran at a ratio of 10mmol:10mL isocyanatepropyltriethoxysilane is added dropwise while stirring. The dropping rate is controlled to be 1 drop / s. After the addition is completed, the mixture is heated to reflux and the stirring reaction is continued for 10h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. Then, the mixture is eluted with a mixed solvent of petroleum ether and ethyl acetate in a volume ratio of 25:1 to obtain a strong modifier;

[0039] Step S2: 2 g of nano zirconium oxide powder with an average particle size of 50 nm and 15 mL of toluene are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 20 min at an ultrasonic power of 300 W, and then 10 mL of a strong modifier solution formed by dissolving 1 g:8 g of a strong modifier in an ethanol solution with a volume fraction of 85% is added and ultrasonically treated for 5 min, and then stirred for 20 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then stirred for 1 h at a temperature of 80° C. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed twice with methanol, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 1 h to obtain modified nano zirconium oxide;

[0040] Step S3: 20 mmol of p-methoxybromobenzene, 10 mmol of p-methoxyaniline, 0.1 g of bis(triphenylphosphino)palladium acetate (II), 0.18 g of 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 2.8 g of tert-butyl potassium and 50 mL of N,N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 100° C. and the stirring reaction was continued for 3 h, and then the mixture was heated to 160° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then allowed to stand to precipitate, and then centrifuged. The precipitate was recrystallized from anhydrous methanol to obtain an intermediate;

[0041] Step S4: 10 mmol of the intermediate and 40 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction for 40 min at a temperature of -5°C and a stirring rate of 300 r / min, and then 4.8 mL of boron tribromide was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was added to ice water, and then vacuum filtered. The filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 70°C for 2 h to obtain a hyperbranched monomer;

[0042] Step S5: 0.1 mol of a hyperbranched monomer, 0.04 mol of bisphenol AF, 0.5 mol of 2,6-dichlorobenzonitrile, 0.2 mol of anhydrous potassium carbonate, 180 mL of N-methylpyrrolidone and 100 mL of toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted at a temperature of 25° C. and a stirring rate of 300 r / min for 1 hour, and then the mixture is heated to 140° C. and the stirring reaction is continued for 3 hours, and then the mixture is heated to 190° C. and the stirring reaction is continued for 3 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to a hydrochloric acid solution with a mass fraction of 5%, and then allowed to stand to precipitate, and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 90° C. for 2 hours to obtain a performance coating resin;

[0043] Step S6: 2 kg of performance coating resin, 0.05 kg of propylene glycol and 80 L of N, N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred and reacted for 3 hours at a temperature of 25°C and a stirring rate of 300 r / min. Then, 5 kg of Toray PAN-P-1.5K carbon fiber cloth with a thickness of 0.18 mm was added and ultrasonically treated for 2 hours at an ultrasonic power of 100 W. Then, the mixture was allowed to stand for 3 hours, and then placed in a vacuum drying oven and dried for 8 hours at a temperature of 80°C to obtain a cut-resistant layer.

[0044] Step S7: 40 parts of polyurethane emulsion, 26 parts of nitrile latex, 1.8 parts of modified nano zirconium oxide, 0.2 parts of cross-linking agent, 1 part of surfactant and 1 part of thickener are weighed in parts by weight for later use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0045] Step S8: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing at a temperature of 25° C. and a stirring rate of 300 r / min for 1 h to obtain a dipping material;

[0046] Step S9: Bond the skin-friendly comfort layer and the cut-resistant layer made of cotton fabric to form a glove blank, and immerse the glove blank in a coagulant prepared by mixing calcium nitrate and methanol in a mass ratio of 1g:95g, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at 60°C for 35 minutes, then heat it to 125°C and dry it for 1 hour, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

[0047] Embodiment 2:

[0048] This embodiment is a method for preparing cut-resistant gloves, comprising the following steps:

[0049] Step S1: 10mmol hydroquinone, 0.015g triethylamine and 52mL anhydrous tetrahydrofuran are added to a four-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28°C and a stirring rate of 350r / min for 25min, and then 22mL of an isocyanatepropyltriethoxysilane solution formed by dissolving isocyanatepropyltriethoxysilane in anhydrous tetrahydrofuran at a ratio of 10mmol:10mL isocyanatepropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 12h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then eluted with a mixed solvent of petroleum ether and ethyl acetate in a volume ratio of 28:1 to obtain a strong modifier;

[0050] Step S2: 2 g of nano zirconium oxide powder with an average particle size of 50 nm and 18 mL of toluene are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 25 min at an ultrasonic power of 325 W, and then 12 mL of a strong modifier solution formed by dissolving the strong modifier in an ethanol solution with a volume fraction of 88% at a ratio of 1 g:9 g is added, and ultrasonic treatment is continued for 8 min, and then stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the temperature is raised to 82° C. and the stirring reaction is continued for 1.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed twice with methanol, and then placed in a vacuum drying oven, and dried at a temperature of 52° C. for 1 h to obtain modified nano zirconium oxide;

[0051] Step S3: 20 mmol of p-methoxybromobenzene, 10 mmol of p-methoxyaniline, 0.11 g of bis(triphenylphosphino)palladium acetate (II), 0.2 g of 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 3.2 g of tert-butyl potassium and 52 mL of N,N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 105° C. and the stirring reaction was continued for 3.5 h, and then the mixture was heated to 165° C. and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then allowed to stand to precipitate, and then centrifuged. The precipitate was recrystallized from anhydrous methanol to obtain an intermediate;

[0052] Step S4: 10 mmol of the intermediate and 45 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction for 45 min at a temperature of -3°C and a stirring rate of 350 r / min, and then 5.7 mL of boron tribromide was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was added to ice water, and then vacuum filtered. The filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 72°C for 2.5 h to obtain a hyperbranched monomer;

[0053] Step S5: 0.2 mol of hyperbranched monomer, 0.05 mol of bisphenol AF, 0.5 mol of 2,6-dichlorobenzonitrile, 0.35 mol of anhydrous potassium carbonate, 190 mL of N-methylpyrrolidone and 110 mL of toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 1.5 h, and then the mixture is heated to 145° C. and the stirring reaction is continued for 3.5 h, and then the mixture is heated to 195° C. and the stirring reaction is continued for 3.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to a hydrochloric acid solution with a mass fraction of 6%, and then allowed to stand to precipitate, and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 95° C. for 2.5 h to obtain a performance coating resin;

[0054] Step S6: 2 kg of performance coating resin, 0.08 kg of propylene glycol and 85 L of N, N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 3.5 hours. Then, 5 kg of Toray PAN-P-1.5K carbon fiber cloth with a thickness of 0.18 mm was added and ultrasonically treated for 2.5 hours at an ultrasonic power of 125 W. Then, the mixture was allowed to stand for 4 hours, and then placed in a vacuum drying oven and dried at a temperature of 82° C. for 9 hours to obtain a cut-resistant layer.

[0055] Step S7: 45 parts of polyurethane emulsion, 34 parts of nitrile latex, 6 parts of modified nano zirconium oxide, 0.4 parts of cross-linking agent, 2 parts of surfactant and 3 parts of thickener are weighed in parts by weight for later use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0056] Step S8: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing at a temperature of 28° C. and a stirring rate of 350 r / min for 1.5 h to obtain a dipping material;

[0057] Step S9: Bond the skin-friendly comfort layer and the cut-resistant layer made of cotton fabric to form a glove blank, and immerse the glove blank in a coagulant prepared by mixing calcium nitrate and methanol in a mass ratio of 5.5 g:95 g, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at a temperature of 62°C for 38 minutes, then heat it to 128°C and dry it for 1 hour, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

[0058] Embodiment 3:

[0059] This embodiment is a method for preparing cut-resistant gloves, comprising the following steps:

[0060] Step S1: 10mmol hydroquinone, 0.02g triethylamine and 55mL anhydrous tetrahydrofuran are added to a four-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then 25mL isocyanatepropyltriethoxysilane solution formed by dissolving isocyanatepropyltriethoxysilane in anhydrous tetrahydrofuran at a ratio of 10mmol:10mL isocyanatepropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the mixture is heated to reflux and the stirring reaction is continued for 15h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then eluted with a mixed solvent of petroleum ether and ethyl acetate in a volume ratio of 30:1 to obtain a strong modifier;

[0061] Step S2: 2 g of nano zirconium oxide powder with an average particle size of 50 nm and 20 mL of toluene are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 30 min at an ultrasonic power of 350 W, and then 15 mL of a strong modifier solution formed by dissolving the strong modifier in a volume fraction of 90% ethanol solution at a ratio of 1 g:10 g is added, and ultrasonic treatment is continued for 10 min, and then the mixture is stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 85° C. and stirred for 2 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed with methanol 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 1.5 h to obtain modified nano zirconium oxide;

[0062] Step S3: 20 mmol of p-methoxybromobenzene, 10 mmol of p-methoxyaniline, 0.12 g of bis(triphenylphosphino)palladium acetate (II), 0.22 g of 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 3.6 g of tert-butyl potassium and 55 mL of N,N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 110° C. and the stirring reaction was continued for 4 h, and then the mixture was heated to 170° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then allowed to stand to precipitate, and then centrifuged. The precipitate was recrystallized from anhydrous methanol to obtain an intermediate;

[0063] Step S4: 10 mmol of the intermediate and 50 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction for 50 min at a temperature of 0° C. and a stirring rate of 400 r / min, and then 6.6 mL of boron tribromide was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was added to ice water, and then vacuum filtered. The filter cake was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75° C. for 3 h to obtain a hyperbranched monomer;

[0064] Step S5: 0.3 mol of a hyperbranched monomer, 0.06 mol of bisphenol AF, 0.5 mol of 2,6-dichlorobenzonitrile, 0.5 mol of anhydrous potassium carbonate, 200 mL of N-methylpyrrolidone and 120 mL of toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 2 h at a temperature of 30° C. and a stirring rate of 400 r / min, and then the mixture is heated to 150° C. and the stirring reaction is continued for 4 h, and then the mixture is heated to 200° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to a hydrochloric acid solution with a mass fraction of 7%, and then allowed to stand to precipitate, and then centrifuged. The precipitate is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 100° C. for 3 h to obtain a high-performance coating resin;

[0065] Step S6: 2 kg of performance coating resin, 0.1 kg of propylene glycol and 90 L of N, N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred and reacted for 4 hours at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 5 kg of Toray PAN-P-1.5K carbon fiber cloth with a thickness of 0.18 mm was added and ultrasonically treated for 3 hours at an ultrasonic power of 150 W. Then, the mixture was allowed to stand for 5 hours, and then placed in a vacuum drying oven and dried for 10 hours at a temperature of 85° C. to obtain a cut-resistant layer.

[0066] Step S7: 50 parts of polyurethane emulsion, 42 parts of nitrile latex, 10.2 parts of modified nano zirconium oxide, 0.6 parts of cross-linking agent, 3 parts of surfactant and 5 parts of thickener are weighed according to weight parts for use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0067] Step S8: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing at a temperature of 30° C. and a stirring rate of 400 r / min for 2 h to obtain a dipping material;

[0068] Step S9: Bond the skin-friendly comfort layer and the cut-resistant layer made of cotton fabric to form a glove blank, and immerse the glove blank in a coagulant prepared by mixing calcium nitrate and methanol in a mass ratio of 10g:95g, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at a temperature of 65°C for 40 minutes, then heat it to 130°C and dry it for 1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

[0069] Comparative Example 1:

[0070] This comparative example is a method for preparing cut-resistant gloves, comprising the following steps:

[0071] Step S1: 50 parts of polyurethane emulsion, 42 parts of nitrile latex, 0.6 parts of cross-linking agent, 3 parts of surfactant and 5 parts of thickener are weighed according to weight parts for use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0072] Step S2: adding polyurethane emulsion, nitrile latex, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing at a temperature of 30° C. and a stirring rate of 400 r / min for 2 h to obtain a dipping material;

[0073] Step S3: immerse the skin-friendly comfort layer made of cotton fabric in a coagulant mixed with calcium nitrate and methanol in a mass ratio of 10g:95g, take it out and immerse it in the dipping material, then place it in a vacuum drying oven, dry it at a temperature of 65°C for 40 minutes, then heat it to 130°C and dry it for 1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain anti-cut gloves.

[0074] Comparative Example 2:

[0075] This comparative example is a method for preparing cut-resistant gloves, comprising the following steps:

[0076] Step S1: 10mmol hydroquinone, 0.02g triethylamine and 55mL anhydrous tetrahydrofuran are added to a four-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then 25mL isocyanatepropyltriethoxysilane solution formed by dissolving isocyanatepropyltriethoxysilane in anhydrous tetrahydrofuran at a ratio of 10mmol:10mL isocyanatepropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the mixture is heated to reflux and the stirring reaction is continued for 15h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then eluted with a mixed solvent of petroleum ether and ethyl acetate in a volume ratio of 30:1 to obtain a strong modifier;

[0077] Step S2: 2 g of nano zirconium oxide powder with an average particle size of 50 nm and 20 mL of toluene are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 30 min at an ultrasonic power of 350 W, and then 15 mL of a strong modifier solution formed by dissolving the strong modifier in a volume fraction of 90% ethanol solution at a ratio of 1 g:10 g is added, and ultrasonic treatment is continued for 10 min, and then the mixture is stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 85° C. and stirred for 2 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed with methanol 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 1.5 h to obtain modified nano zirconium oxide;

[0078] Step S3: 50 parts of polyurethane emulsion, 42 parts of nitrile latex, 10.2 parts of modified nano zirconium oxide, 0.6 parts of cross-linking agent, 3 parts of surfactant and 5 parts of thickener are weighed in parts by weight for later use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0079] Step S4: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing at a temperature of 30° C. and a stirring rate of 400 r / min for 2 h to obtain a dipping material;

[0080] Step S5: immerse the skin-friendly comfort layer made of cotton fabric material in a coagulant mixed with calcium nitrate and methanol in a mass ratio of 10g:95g, take it out and immerse it in the dipping material, then place it in a vacuum drying oven, dry it at a temperature of 65°C for 40 minutes, then heat it to 130°C and dry it for 1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain anti-cut gloves.

[0081] Comparative Example 3:

[0082] This comparative example is a method for preparing cut-resistant gloves, comprising the following steps:

[0083] Step S1: 20 mmol of p-methoxybromobenzene, 10 mmol of p-methoxyaniline, 0.12 g of bis(triphenylphosphino)acetate palladium(II), 0.22 g of 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 3.6 g of tert-butyl potassium and 55 mL of N,N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 110° C. and the stirring reaction was continued for 4 h, and then the mixture was heated to 170° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then allowed to stand to precipitate, and then centrifuged. The precipitate was recrystallized from anhydrous methanol to obtain an intermediate;

[0084] Step S2: 10 mmol of the intermediate and 50 mL of chloroform are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture is stirred for reaction for 50 min at a temperature of 0° C. and a stirring rate of 400 r / min, and then 6.6 mL of boron tribromide is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is added to ice water, and then vacuum filtered. The filter cake is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75° C. for 3 h to obtain a hyperbranched monomer;

[0085] Step S3: 0.3 mol of a hyperbranched monomer, 0.06 mol of bisphenol AF, 0.5 mol of 2,6-dichlorobenzonitrile, 0.5 mol of anhydrous potassium carbonate, 200 mL of N-methylpyrrolidone and 120 mL of toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 2 h at a temperature of 30° C. and a stirring rate of 400 r / min, and then the mixture is heated to 150° C. and the stirring reaction is continued for 4 h, and then the mixture is heated to 200° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to a hydrochloric acid solution with a mass fraction of 7%, and then allowed to stand to precipitate, and then centrifuged. The precipitate is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 100° C. for 3 h to obtain a high-performance coating resin;

[0086] Step S4: 2 kg of performance coating resin, 0.1 kg of propylene glycol and 90 L of N, N'-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred and reacted for 4 hours at a temperature of 30°C and a stirring rate of 400 r / min. Then, 5 kg of Toray PAN-P-1.5K carbon fiber cloth with a thickness of 0.18 mm was added and ultrasonically treated for 3 hours at an ultrasonic power of 150 W. Then, the mixture was allowed to stand for 5 hours, and then placed in a vacuum drying oven and dried for 10 hours at a temperature of 85°C to obtain a cut-resistant layer.

[0087] Step S5: 50 parts of polyurethane emulsion, 42 parts of nitrile latex, 0.6 parts of cross-linking agent, 3 parts of surfactant and 5 parts of thickener are weighed in parts by weight for later use; the polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose;

[0088] Step S6: adding the polyurethane emulsion, nitrile latex, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing for 2 hours at a temperature of 30° C. and a stirring rate of 400 r / min to obtain a dipping material;

[0089] Step S7: Bond the skin-friendly comfort layer and the cut-resistant layer made of cotton fabric to form a glove blank, and immerse the glove blank in a coagulant prepared by mixing calcium nitrate and methanol in a mass ratio of 10g:95g, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at a temperature of 65°C for 40 minutes, then heat it to 130°C and dry it for 1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

[0090] The cut-resistant gloves in Examples 1-3 and Comparative Examples 1-3 were tested for cut resistance, tear resistance and puncture resistance according to standard GB24541-2009. The test results are shown in the following table:

[0091] sample Cutting resistance, index Tear resistance, N Puncture resistance, N Example 1 22.8 79 154 Example 2 24.1 81 159 Example 3 25.5 84 163 Comparative Example 1 5.2 38 74 Comparative Example 2 12.4 53 101 Comparative Example 3 21.8 71 146

[0092] Referring to the data in the above table, it can be seen that adding a strong modifier and using a cut-resistant layer can significantly improve the cut-resistant and puncture-resistant performance of cut-resistant gloves, and the best effect is achieved under the synergistic effect of the two.

[0093] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0094] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A cut-resistant glove, characterized in that: From inside to outside, there are skin-friendly comfort layer, cut-resistant layer and wear-resistant rubber layer. Wherein, the cut-resistant layer is prepared by the following steps: Step s1: stirring p-methoxybromobenzene, p-methoxyaniline, bis(triphenylphosphino)acetate palladium(II), 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, tert-butyl potassium and N,N'-dimethylacetamide for reaction, cooling the reaction product after the reaction, then adding it into ice water, then standing to precipitate, then centrifuging, and recrystallizing the precipitate to obtain an intermediate; Step s2: stirring the intermediate and chloroform to react, then adding boron tribromide dropwise while stirring, and continuing to stir the reaction after the dropwise addition is completed. After the reaction is completed, adding the reaction product into ice water, and then vacuum filtering, washing and drying the filter cake to obtain a hyperbranched monomer; Step s3: stirring a hyperbranched monomer, bisphenol AF, 2,6-dichlorobenzonitrile, anhydrous potassium carbonate, N-methylpyrrolidone and toluene for reaction, cooling the reaction product after the reaction is completed, then adding it to a hydrochloric acid solution, then standing it to precipitate, then centrifuging it, washing and drying the precipitate to obtain a performance coating resin; Step s4: stirring the performance coating resin, propylene glycol and N,N'-dimethylacetamide for reaction, then adding the carbon fiber cloth and performing ultrasonic treatment, then standing and drying to obtain a cut-resistant layer.

2. The cut-resistant glove according to claim 1, characterized in that: The amount ratio of p-methoxybromobenzene, p-methoxyaniline, bis(triphenylphosphino)acetate palladium(II), 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, tert-butyl potassium and N,N'-dimethylacetamide in step s1 is 20mmol:10mmol:0.1-0.12g:0.18-0.22g:2.8-3.6g:50-55mL.

3. The cut-resistant glove according to claim 1, characterized in that: The usage ratio of the intermediate, chloroform and boron tribromide in step s2 is 10 mmol:40-50 mL:4.8-6.6 mL.

4. The cut-resistant glove according to claim 1, characterized in that: The usage ratio of the hyperbranched monomer, bisphenol AF, 2,6-dichlorobenzonitrile, anhydrous potassium carbonate, N-methylpyrrolidone and toluene in step s3 is 0.1-0.3 mol: 0.04-0.06 mol: 0.5 mol: 0.2-0.5 mol: 180-200 mL: 100-120 mL; the mass fraction of the hydrochloric acid solution is 5-7%.

5. The cut-resistant glove according to claim 1, characterized in that: The usage ratio of the performance coating resin, glycerol, N,N'-dimethylacetamide and carbon fiber cloth in step s4 is 2g:0.05-0.1g:80-90mL:5g; the carbon fiber cloth is Toray PAN-P-1.5K plain carbon fiber woven cloth with a thickness of 0.18mm.

6. A method for preparing cut-resistant gloves, characterized in that: The following steps are involved: Step 1: Weigh 40-50 parts of polyurethane emulsion, 26-42 parts of nitrile latex, 1.8-10.2 parts of modified nano zirconium oxide, 0.2-0.6 parts of cross-linking agent, 1-3 parts of surfactant and 1-5 parts of thickener according to weight parts, and set aside; Step 2: adding polyurethane emulsion, nitrile latex, modified nano zirconium oxide, crosslinking agent, surfactant and thickener into a mixer, stirring and mixing for 1-2 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min to obtain a dipping material; Step 3: Bond the skin-friendly comfort layer and the cut-resistant layer to form a glove blank, and immerse the glove blank in a coagulant, take it out and immerse it in a dipping material, then place it in a vacuum drying oven, dry it at a temperature of 60-65°C for 35-40 minutes, then heat it to 125-130°C and dry it for 1-1.5 hours, solidify it to form a wear-resistant dipping layer, and obtain a cut-resistant glove.

7. The method for preparing cut-resistant gloves according to claim 6, characterized in that: The polyurethane emulsion is WPU-125 water-based polyurethane emulsion; the nitrile latex is HT-830 water-based nitrile latex; the cross-linking agent is a polycarbodiimide cross-linking agent; the surfactant is sodium dodecyl sulfate; the thickener is sodium carboxymethyl cellulose; the skin-friendly comfort layer is one of polyester fabric, cotton fabric, linen fabric, acrylic fabric and nylon fabric; the coagulant is a mixed solution of calcium nitrate and methanol in a mass ratio of 1-10g:95g.

8. The method for preparing cut-resistant gloves according to claim 6, characterized in that: The modified nano zirconium oxide is prepared by the following steps: Step a1: stirring hydroquinone, triethylamine and anhydrous tetrahydrofuran for reaction, then adding isocyanate propyl triethoxysilane solution dropwise while stirring, and continuing to stir the reaction after the addition is completed. After the reaction is completed, the reaction product is cooled, then rotary evaporated, and then eluted with a mixed solvent to obtain a strong modifier; Step a2: subjecting nano zirconium oxide powder and toluene to ultrasonic treatment, then adding a strong modifier solution and continuing the ultrasonic treatment, then stirring the reaction, cooling the reaction product after the reaction is completed, then centrifuging, washing and drying the precipitate to obtain modified nano zirconium oxide.

9. The method for preparing cut-resistant gloves according to claim 8, characterized in that: The amount ratio of the hydroquinone, triethylamine, anhydrous tetrahydrofuran and isocyanate propyl triethoxysilane solution in step a1 is 10mmol:0.01-0.02g:50-55mL:20-25mL; the isocyanate propyl triethoxysilane solution is a solution formed by dissolving isocyanate propyl triethoxysilane in anhydrous tetrahydrofuran at a ratio of 10mmol:10mL; the mixed solvent is a mixture of petroleum ether and ethyl acetate at a volume ratio of 25-30:

1.

10. The method for preparing cut-resistant gloves according to claim 8, characterized in that: The dosage ratio of the nano zirconium oxide powder, toluene and strong modifier solution in step a2 is 2g:15-20mL:10-15mL; the average particle size of the nano zirconium oxide powder is 50nm; the strong modifier solution is a mixture formed by dissolving the strong modifier in an ethanol solution at a ratio of 1g:8-10g, and the volume fraction of the ethanol solution is 85-90%.

Citation Information

Patent Citations

  • Foaming glove and production method thereof

    CN109457489A

  • Wear-resistant antiskid latex glove and making method thereof

    CN109796640A

  • Production technology of macromolecular nano-composite stab-resistant fabric

    CN110834440A

  • Anti-cutting polyurethane impregnated latex protective gloves and preparation process thereof

    CN114381048A

  • High-strength cutting-resistant working gloves and preparation method thereof

    CN117944308A

Cited By

  • Flexible rollable lap joint type stab-resistant layer, stab-resistant garment and preparation method of stab-resistant garment

    CN119969672A

  • Hydrophobic protective glue and preparation method thereof

    CN120888269A